تآكل المنشآت المعدنية - علي غسان شيخ; ندّاف قصي; ساحللي سامر (Latakia University Journal -Engineering Sciences Series, 2019)
تكتسب ظاهرة تآكل الفولاذ أهمية خاصة نتيجة انتشارها الواسع في المنشآت الفولاذية المقامة في المنطقة الساحلية والتي أصبحت تشكل خطراً كبيراً على أمن بعض المنشآت المذكورة بالإضافة إلى تكاليف الصيانة الدورية المرتفعة. و يبيّن هذا البحث بعض أنواع تآكل الفولاذ مع شرح مبسط لآلية حدوث كل نوع من هذه الأنواع وأسبابه بغية اختيار أفضل الطرق لمعالجة هذه الظاهرة، سوف نعرض كما كما يعرض بعض الأمثلة التي وجدها الباحث في عدد من المنشآت المعدنية في الساحل السوري. The corrosion of steel phenomenon has special importance because of its great spread in the steel structures which are built in the costal areas, the thing that imposes a great danger on the safety of these structures, in addition to the high costs of the periodic maintenance. This study demonstrates some kinds of steel corrosion with a simple explanation of the mechanism and the reasons of corrosion in order to choose the best ways to treat this phenomenon, with a demonstration of some examples that are found in some steel constructions on the Syrian coast.